Nitrogen content of pea‐based cover crop mixtures and subsequent organic corn yield. (29th June 2021) - Lavergne, Stéphanie; Vanasse, Anne; Thivierge, Marie‐Noëlle; Halde, Caroline
Abstract: Organic growers rely heavily on manure additions to meet corn ( Zea mays L.) nitrogen (N) needs. Considering the limited availability of farmyard manure and its increasing cost, the use of cover crop mixtures may help in addressing this challenge. The impact of fall‐seeded cover crops with or without pelletized poultry manure application on corn yield and N dynamics was investigated at three sites in Québec, Canada. Cover crop treatments consisted of field pea ( Pisum sativum L.) in a pure stand, 2‐, 6‐, and 12‐species pea‐based mixtures, and a weedy control without cover crops. Nitrogen content of shoot biomass was the greatest for the pure stand of field pea at Augustin17 (157 kg N ha –1 ), and for the pure stand of field pea and the 2‐species mixture at Augustin18 (average of 109 kg N ha –1 ) and Barthelemy17 (average of 171 kg N ha –1 ). Nitrogen content of root biomass averaged 13 kg N ha –1 . Cover crops increased organic corn grain yield by 28% compared to a weedy control. Corn grain yield was similar following the pure stand of field pea and the mixtures of 2 and 12 species, showing no clear advantage of using mixtures instead of a pure stand of field pea regarding N supply and corn yield. Corn yield increased by 10% with poultry manure application irrespective of the cover crop treatments. These results indicate that the use of cover crops, either a pure legume or legume in mixture, could contribute to organic grain corn yield. Core Ideas: Biomass N content of cover crops tended to be the greatest for the pure stand of field pea. Root N content accounted for only 14% total N content of cover crops. Corn grain yield was on average 28% greater with cover crops than the weedy control. Corn yield increased following field pea and 2‐ and 12‐ but not 6‐species mixtures. Adding poultry manure increased corn grain yield by 10% compared to unfertilized corn.